Biodegradability of bioplastic blown film in a marine environment - Phosri, Santi; Kunjiek, Tikumporn; Mukkhakang, Chaninta; Suebthep, Sililuck; Sinsup, Wannisa; Phornsirigarn, Sasithorn; Charoeythornkhajhornchai, Pollawat (Frontiers in Marine Science, 2022)
The waste created by single-use plastics is an important global issue, especially in marine environments, because they do not degrade in nature. This work aimed to study the biodegradability of bioplastic blown film, which may pose a solution to this problem. Polybutylene succinate (PBS) and polylactic acid (PLA) blown films were chosen for examination of their biodegradability when submerged in sand under the seawater and when floated on the seawater surface of our experimental setup. Bioplastics were observed in comparison with low-density polyethylene (LDPE), which is a petroleum-based plastic. PBS blown film exhibited a faster degradation rate than PLA blown film, while LDPE blown film did not degrade in the marine environment. The biodegradability of bioplastic blown film was confirmed by physical observation, a change in the chemical functional group measured by Fourier-transform infrared spectroscopy, and a test of the biochemical oxygen demand of the seawater after bioplastic degradation due to ingestion by bacteria in seawater.